Mapping Strategies for Local Economic Development Using SWOT Analysis to Achieve the SDGs 2030 - A. Wulandari; Aksi Hamzah; Otong Karyono (International Forum of Researchers and Lecturers, 2025)
This study aims to map the strengths, weaknesses, opportunities, and threats (SWOT) of each village within Awangpone Subdistrict to formulate a strategic model for enhancing the local economy in alignment with the Sustainable Development Goals (SDGs) 2030. Employing a qualitative field research design, the study integrates interdisciplinary, theological, and development economics approaches. Data were collected through questionnaires, interviews, direct observation, and documentation. The analysis follows Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing. The SWOT analysis reveals that the coordinates fall within Quadrant I, indicating that strengths outweigh weaknesses and opportunities surpass threats. Accordingly, the recommended strategy is the Strength-Opportunity (S-O) approach, which emphasizes leveraging internal strengths to capitalize on external opportunities. This strategy is deemed most effective for stimulating local economic growth and accelerating SDG achievement. Internal constraints identified include underutilized tourism potential and limited access to sharia-compliant financing mechanisms. External threats comprise weak partnership collaborations and limited foreign investment engagement. While several SDG targets—such as education and community participation—have shown promising progress, others remain underdeveloped, particularly in infrastructure development and equitable access to justice for rural populations. The findings underscore the importance of context-sensitive, multi-sectoral strategies that integrate local wisdom, theological values, and economic principles. The proposed strategic model offers a practical roadmap for village-level economic empowerment, contributing to inclusive and sustainable development. This research provides actionable insights for policymakers, development practitioners, and local stakeholders seeking to optimize village potential and foster resilience in rural economies.